Highly sensitive, tunable, and durable gold nanosheet strain sensors for human motion detection - Lim, Guh-Hwan; Lee, Nae-Eung; Lim, Byungkwon (Journal of materials chemistry. C, Materials for optical and electronic devices, 2016)
We report highly sensitive, tunable, and durable strain sensors based on a simple structure consisting of a multilayered film of gold (Au) nanosheets as a sensing layer on a highly stretchable Ecoflex substrate. The high sensitivity of the sensor at different levels of strain was achieved by controlling the stacking number of micrometer-sized Au nanosheets with a thickness of ∼20 nm, which enabled the control of piezoresisitivity of the sensing layer through the change in contact resistance between Au nanosheets under mechanical bending and stretching. The Au nanosheet-based strain sensors exhibited excellent electrical stability without degradation in sensing-performance even after 10 000 stretching cycles. Our highly sensitive, reproducible, tunable, and durable strain sensors were demonstrated to monitor large-scale body motions such as bending, walking, jumping, and squatting, as well as to detect small skin strains induced by minute movements of muscles upon breathing, speaking, and coughing. We report highly sensitive, tunable, and durable strain sensors based on a simple structure consisting of a multilayered film of gold (Au) nanosheets as a sensing layer on a highly stretchable Ecoflex substrate.